2003
DOI: 10.1007/s00430-003-0177-y
|View full text |Cite
|
Sign up to set email alerts
|

The therapy of virus-associated epithelial tumors of the face and the lips in organ transplant recipients

Abstract: The risk of developing malignant cutaneous neoplasms is increased after organ transplantation. We report three patients with malignant tumors of the epithelium of the facial skin and the lips after kidney and heart transplantation, respectively. They showed an aggressive course of the disease with more than five synchronous or metachronous basal cell and squamous cell carcinomas. Tissue samples were Epstein-Barr virus (EBV) positive by PCR. Using an in situ hybridization technique EBV-encoded RNA (EBER) was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In the present study no clinically malignant alterations in gingival overgrowth were observed. The incidence of squaomous oral carcinoma and basal cell carcinoma is notably increased after organ transplantation (Hyckel et al , 2003). However, the majority of reports regarding carcinoma associated with immunosuppression are related to the skin.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study no clinically malignant alterations in gingival overgrowth were observed. The incidence of squaomous oral carcinoma and basal cell carcinoma is notably increased after organ transplantation (Hyckel et al , 2003). However, the majority of reports regarding carcinoma associated with immunosuppression are related to the skin.…”
Section: Discussionmentioning
confidence: 99%
“…In immunocompromised patients, post-transplant lymphoproliferative disease (PTLD) and AIDS-related lymphomas are observed. Several studies further demonstrate that EBV is involved in the development of certain T-cell and Hodgkin's lymphomas [6,7] and some malignant skin neoplasms in transplant recipients [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…BK virus) and human papilloma virus (HPV) among others [4]. HPV is increasingly seen in organ transplant recipients presenting with warts and condylomata acuminata, as well as neoplastic manifestations which may potentially lead to anal, vulvar, cervical or penile carcinoma [5–7].…”
Section: Introductionmentioning
confidence: 99%